The Underlying Causes of Poverty among Fisherman in Deli Serdang Regency - Nina Novira; Muhammad Arif; Novida Yenny; Nur Saidah Siregar; Desi Permata Sari (Jurnal Ilmu Sosial dan Humaniora, 2024)
Fishermen in Indonesia are generally relatively poor. Low education is widely accepted as the cause, while others appointed terrible habits and bad custom practices as the main contributors. The fishermen are also accused of being lazy and fatalistic and like to waste money if they happen to have a big catch. However, we believe that the problem is not as simple. Therefore, we aim to explore the issue more and seek an understanding of the underlying cause of poverty among fishermen in Indonesia, especially in Percut, Deli Serdang Regency. Designing the study as a qualitative study, we use in-depth interviews to collect data from various actors, such as 39 fishermen, the head of the village, and two hamlet heads. The sampling technique was conducted using the snowball technique. The data analysis method of this research uses daily interpretative analysis. Our results show that the general assumption mentioned above is not valid. They are hard workers and not money wasters. The poverty is caused more by the lack of access to many aspects of life improvement. Poor access to education, poor market access, and poor access to credit institutions; some also have poor access to their primary resource, the sea, since they do not possess adequate equipment for it. These have limited the possibility for fishermen to improve their well-being.